Body Composition Analysis Junior Basketball Players - Solikah, Nur Luthfiatus; Wahyudi, Heri; Widodo, Achmad; Firmansyah, Awang; Muarif, Jagat Shine; Muslim, Asep Aziz (Physical Education and Sports: Studies and Research, 2024)
Background: Athletes must maintain top physical condition to compete, with body composition a crucial indicator. Skeletal muscle mass and body fat are related to performance, with a lower fat percentage increasing physical ability. Nutritional needs also play a role, where athletes consume carbohydrates for 60-70% of their energy. These factors are essential for optimal performance and overall health. Objectives: This study aimed to investigate the body composition of junior basketball athletes regarding gender. Methods: This study employed a rigorous cross-sectional research design to analyze the body composition measurements of elite athletes and junior basketball players. The participants were carefully selected based on age, injury history, national-level achievements, and recent injury training. A total of 24 junior basketball athletes, evenly split between elite junior male and female athletes, participated in the test. The data was meticulously analyzed using Minitab software and the T-test to determine gender differences, ensuring the validity and reliability of the results. Results: The athletes were aged 16-17, weighing 50-65 kg to 95-108 kg. They had BMI characteristics of 8.3% underweight, 79.2% normal, 12.5% overweight, and 0% obese. Significant differences were found in body composition characteristics for each gender. The T-test results show significant differences between the variables with a P value <0.05.   Conclusion: They indicate that female basketball athletes tend to have a higher fat percentage, while male athletes typically possess significantly greater muscle mass. These insights can be instrumental in developing gender-specific training and nutrition programs, thereby enhancing the performance and health of junior basketball athletes.